Discordance in investigator-reported and adjudicated sudden death in TIOSPIR - Wise, Robert A. (ERJ Open Res, 2017)
Accurate and consistent determination of cause of death is challenging in chronic obstructive pulmonary disease (COPD) patients. TIOSPIR (N=17 135) compared the safety and efficacy of tiotropium Respimat 5/2.5 µg with HandiHaler 18 µg in COPD patients. All-cause mortality was a primary end-point. A mortality adjudication committee (MAC) assessed all deaths. We aimed to investigate causes of discordance in investigator-reported and MAC-adjudicated causes of death and their impact on results, especially cardiac and sudden death. The MAC provided independent, blinded assessment of investigator-reported deaths (n=1302) and assigned underlying cause of death. Discordance between causes of death was assessed descriptively (shift tables). There was agreement between investigator-reported and MAC-adjudicated deaths in 69.4% of cases at the system organ class level. Differences were mainly observed for cardiac deaths (16.4% investigator, 5.1% MAC) and deaths assigned to general disorders including sudden death (17.4% investigator, 24.6% MAC). Reasons for discrepancies included investigator attribution to the immediate (e.g. myocardial infarction (MI)) over the underlying cause of death (e.g. COPD) and insufficient information for a definitive cause. Cause-specific mortality varies in COPD, depending on the method of assignment. Sudden death, witnessed and unwitnessed, is common in COPD and often attributed to MI without supporting evidence.